Pengaruh Disiplin Kerja Dan Stres Kerja Terhadap Kinerja Pegawai UPTD Puskesmas Sambi Kab. Kediri - Erika Priya Ningtias; Ahmad Jauhari; Nur Hidayati (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
This research is motivated that in institutions engaged in the health sector, in this organization human resources are very important in achieving the goals and success of the agency. This study aims to determine the influence of work discipline and work stress on employee performance. This study used quantitative methods. The sampling technique uses Nonprobability Sampling with a saturated sampling method of 47 employees. Testing in this study using SPSS software program version 25.0. The analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, F test and determination coefficient test. The results of this study show that partially the variable of work discipline has a positive and significant effect on employee performance with a calculated tvalue of 3.059>ttable 2.01537 with a signification value of 0.004<0.05 and partially the variable of work stress has a positive and significant effect with a calculated tvalue of 2.468>ttable 2.01537 with a signification value of 0.018<0.05, simultaneously the variables of work discipline and work stress have a positive and significant effect on employee performance with a calculated Fvalue of 8.265>Ftable 3.21 with a signification value of 0.001<0.05.